Species richness and distributional pattern of amphibians along an elevational gradient at Gunung Raya, Pulau Langkawi, Kedah, Malaysia - Ehwan N.,; Nur Johana J.,; Shukor M.N.,; Yaakop S.,; Grismer, L.L.; Norhayati A., (Penerbit Universiti Kebangsaan Malaysia, 2018)
A study on amphibian community at Gunung Raya, Pulau Langkawi was conducted in order to identify amphibian species richness and species distribution pattern along an elevation gradient. Species richness and distribution pattern of amphibians along an elevational gradient could explain factors that determine ecological processes in a particular highland. Passive sampling method by using two types of traps namely Drift- fenced pitfall trap and PVC pipe trap were used from February 2014 until January 2015. 100 individual comprise of 10 species amphibian were recorded. Leptobrachium smithii were the most abundant (n=37) followed by Megophrys aceras (n=28). Rank abundance curve for amphibian community show a Broken Stick pattern (χ2=12.67, p=0.12). Species accumulation curve does not level off to an asymptote, indicating insufficient sample size despite intensive sampling effort. Estimation analysis by using Chao 1 predictor produces 12 amphibian species based on 100 pooled individuals. A weak positive exponential function fits the distribution pattern of amphibian abundance (y=0.0028x+13.39), reflecting species domination towards the peak. A negative exponential function fits distribution pattern of amphibian species number across the elevation gradient (y=-0.0091x+7.247), due to the lack of permanent water resource at the upper elevation. These results indicated that by understanding the upland ecology of amphibians, important decisions may be critical for designing conservation efforts and planning land use.